The Night-Side of Zangskar: Spirits, Landscape, and the Uncanny - Pearce, Callum (Material religion, 2020)
Anthropological discussions of place and landscape have tended to be dominated by a focus on the Heideggerian concept of “dwelling”, with an emphasis on values of wisdom, belonging and connectedness. This approach privileges descriptions of knowledge and harmony over those of uncertainty and fear, with the effect of obscuring the less positive associations of landscape. In this article, drawing on fieldwork in the predominantly Buddhist valley of Zangskar in the western Indian Himalaya, I will suggest that local stories of encounters with spirits instead demonstrate a sense of the “uncanny”: a disorienting mingling of the familiar and the strange that emerges from the limitations of ordinary human knowledge and perception. The Zangskari landscape encompasses hidden places and villages of semi-human beings, and when night falls it takes on another aspect: in encounters with spirits and the “hidden people”, boundaries are dissolved and the categories of the strange and the familiar are collapsed. These beings take on almost-human forms and project both an ambiguous familiarity and a basic otherness, revealed in the darkness, that stands behind the appearances of day.